Analisis Penerapan Key Performance Indicator Sebagai Sistem Penilaian Kinerja Karyawan di PT Sunio Citra Teknologi Kota Tangerang - Saputri, Shintya Tjandra; Indriyani, Furi (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
This study aims to analyze the implementation of Key Performance Indicators (KPI) as an employee performance appraisal system at PT Sunio Citra Teknologi, Tangerang City. The research uses a descriptive non-statistical method with a field research approach. Data were collected through observation, documentation, and semi-structured interviews with 31 employees from Sales, Admin & Finance, and IT & Support divisions. The findings indicate that KPI implementation provides clearer work direction, improves discipline, and enhances accountability. However, several challenges remain, including inconsistent monitoring and limited integration of KPI results into reward systems. The study concludes that KPI has functioned as a performance measurement tool, but refinement of evaluation mechanisms is necessary to improve organizational productivity